Licking induced changes to the pattern of moxidectin milk elimination after topical treatment in dairy cows - Imperiale, Fernanda Andrea (2009)
Pour-on administration of the macrocyclic lactones anti-parasitic compounds in beef and dairy cattle is now worldwide accepted. However, the information available on their milk excretion pattern, after topical administration is rather limited. Additionally, the cattle licking behaviour has been proven to affect the kinetics of these anti-parasitic compounds. The purpose of this study was to investigate the influence of the natural licking behaviour on the plasma and milk disposition of moxidectin (MXD), topically administered (500 μg/kg) in lactating dairy cows. Ten lactating Holstein dairy cows (705 kg body weight) were allocated into two experimental groups (n = 5). The licking was prevented during 5 days postadministration in animals in group I, and the remaining cows (group II) were allowed to lick freely. MXD concentrations profiles were measured in plasma and milk over 15 days posttreatment. The licking restriction period caused marked changes in MXD disposition kinetics both in plasma and milk. Both plasma and milk MXD concentrations (partial AUC 0-5 days) were significantly lower (P < 0.05) in licking-restricted cows. After the 5-day of restriction period, the animals were allowed to lick freely, which permitted the oral ingestion of MXD, situation clearly reflected both in plasma profile and milk excretion pattern. Despite the enhanced MXD milk concentrations measured in free-licking cows, drug concentrations did not reach the maximum MXD residues limit.